Somatic Embryogenesis of Populus deltoides - (:unkn) unknown (ARS DOCENDI, 2012)
Node, internode, and leaf explants of Populus deltoides Bartr. ex Marsh. x Populus deltoides Bartr. ex Marsh. hybrid poplar clone (89 M 066) tissue culture regenerated plantlets were used for direct and indirect somatic embryogenesis. Direct somatic embryos were differentiated on node, internode and leaf explants on Murashige and Skoog basal medium (MS) supplemented with N-6-Benzyladenine (BA) and 2,4-Dichlorophenoxy acetic acid (2,4-D). The best somatic embryogenesis observed on MS medium supplemented with 0.05 mg/l BA and 5 mg/l 2,4-D with internodes explants in darkness within 3 weeks. Embryogenic calli formation for the first step of indirect regeneration were obtained on node, internode and leaf explants on MS with 2,4-D or MS with 1-Phenyl-3-(1,2,3-thiadiazol-5-yl) urea (TDZ) and Coconut Water (CW). Internode explants gave the best result (100%) for embryogenic calli formation on MS with 0.8 or 1 mg/l TDZ with 2% CW after 3 weeks. Subsequent transfer of internode-derived embryogenic calli on the same media resulted in somatic embryogenesis within 2 weeks with the frequency of 33% on MS with 0.8 mg/l TDZ with 2% CW. Further development of embryos to the torpedo stage was obtained by subculturing on the same medium. There after, germination of the direct somatic embryos were achieved on Woody Plant Medium (WPM) supplemented with 1 mg/l zeatine in 3 weeks. Data in the study were subjected to statistical evaluation. These systems could be useful for rapid clonal propagation via somatic embryogenesis of eastern cottonwood clones.
Keywords: Populus deltoides; Poplar; Eastern Cottonwood; Tissue culture; Regeneration; Somatic embryogenesis; PLANT-REGENERATION; TISSUE-CULTURES; LEAF; FREQUENCY; INDUCTION; EXPLANTS; IMMATURE; TREE